INTEGRASI INTERKONEKSI PERMAINAN CONGKAK DENGAN QURAN SEBAGAI PENDIDIKAN KARAKTER ANAK DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Muhammad Ikhsan Attaftazani; Andika Setiawan (Universitas Muhammadiyah Ponorogo, 2020)
Entering the era of industrial revolution 4.0, technology is growing rapidly and has a significant influence on life in Indonesia, especially for children. Accessing the internet to do homework from the school is sometimes misused by them due to a lack of guidance in accessing them, such as accessing immoral videos. According to Susanto, Chair of the Indonesian Child Protection Commission (KPAI), in 2018 counted until September there were 525 cases of pornography and cybercrime in children. One of the efforts that can be done in overcoming it is through character education that is inspired by surah Al-Isra (17): 32 and Al-Tahrim (66): 6 which instructs to guard themselves and their families from bad deeds, especially zina. The form of Quran character education will be taught using a traditional game in the form of dakon or congkak. The research method in this paper uses direct observation in several schools in the Yogyakarta area. This study uses qualitative data with primary and secondary sources. The technique of collecting data uses literature review, documentation, and interviews with elementary school (SD) level students. The purpose of this research is to improve the quality of children in education and advance the nation's next-generation in various ways. With the game dakon or congkak, later it will be explained about babakan hawa sanga or closing nine holes in the body. The game will be integrated with the Quranic values by explaining the verses of the Quran that are following the game.